EHMT1/EHMT2 in EMT, cancer stemness and drug resistance: emerging evidence and mechanisms. (8th January 2022) - Nachiyappan, Alamelu; Gupta, Neelima; Taneja, Reshma
Abstract : Metastasis, therapy failure and tumour recurrence are major clinical challenges in cancer. The interplay between tumour‐initiating cells (TICs) and epithelial–mesenchymal transition (EMT) drives tumour progression and spread. Recent advances have highlighted the involvement of epigenetic deregulation in these processes. The euchromatin histone lysine methyltransferase 1 (EHMT1) and euchromatin histone lysine methyltransferase 2 (EHMT2) that primarily mediate histone 3 lysine 9 di‐methylation (H3K9me2), as well as methylation of non‐histone proteins, are now recognised to be aberrantly expressed in many cancers. Their deregulated expression is associated with EMT, cellular plasticity and therapy resistance. In this review, we summarise evidence of their myriad roles in cancer metastasis, stemness and drug resistance. We discuss cancer‐type specific molecular targets, context‐dependent mechanisms and future directions of research in targeting EHMT1/EHMT2 for the treatment of cancer. Abstract : The epigenetic modifiers EHMT1 and EHMT2 are deregulated in various cancers. Their roles in EMT, stemness, drug resistance and metabolic adaptation have been linked to tumour progression and aggressiveness. However, their independent roles in these processes, the underlying mechanisms and cancer‐type specific functions need further investigation. Addressing these will aid the development of selective EHMT1 and EHMT2 inhibitors and avenues to regulate downstream pathways and targets.